2015
DOI: 10.5897/ajmr2015.7602
|View full text |Cite
|
Sign up to set email alerts
|

Production of aquatic feed grade algal powder from turtle breeding wastewater using a locally isolated Spirulina sp. JXSC-S1

Abstract: Spirulina sp. JXSC-S1 was isolated from a local turtle breeding wastewater storage pool in Jiaxing City, Zhejiang Province, China. Morphological studies revealed that the color, shape, spiral pitch, spiral wide and cell size of the strain fits the typical morphological characteristics of Spirulina platensis. Growth dynamics of the strain were studied in both Zarrouk medium and turtle breeding wastewater (TBW), and were compared with three S. platensis strains S6, S2 and Ns-90020 that are applied in large-scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The morphological feature of S. platensis identified like a blue-green filamentous cyanobacterium was reported by Luo and Jiang (2015). Microscopic analysis revealed that the number of whorls and filaments are influenced by sulphate salts concentration.…”
Section: Discussionmentioning
confidence: 67%
“…The morphological feature of S. platensis identified like a blue-green filamentous cyanobacterium was reported by Luo and Jiang (2015). Microscopic analysis revealed that the number of whorls and filaments are influenced by sulphate salts concentration.…”
Section: Discussionmentioning
confidence: 67%